Pengembangan Media E-Book Bermuatan Kuliner Sasak pada Mata Pelajaran IPAS untuk Siswa Kelas IV di SDN 2 Dasan Tereng - Helma Urfiani; Moh. Irawan Zain; Ilham Handika (Mataram University, 2026)
This research is motivated by the prevalence of teacher-centered lecture methods and the heavy reliance on national textbooks, alongside the limited utilization of digital media and learning resources based on local wisdom. Furthermore, the lack of variety in instructional media has led to low student learning motivation. Addressing these issues, this study aims to develop a valid and practical educational e-book based on Sasak culinary heritage for Social and Natural Sciences (IPAS subject) instruction among fourth-grade students at SDN 2 Dasan Tereng. The methodology employed is Research and Development (R&D), following the ADDIE development model. Data collection techniques included interviews, observations, and questionnaires, using instruments such as interview guides, observation sheets, and validation scales for material experts, media experts, as well as teacher and student responses. Data analysis was conducted through validity and practicality tests using a 1–4 Likert scale. The results indicate that the developed e-book meets the criteria for being